2019
DOI: 10.1093/infdis/jiz684
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium parvum Elongation Factor 1α Participates in the Formation of Base Structure at the Infection Site During Invasion

Abstract: Background Cryptosporidium is a genus of apicomplexan parasites, the causative agents of cryptosporidiosis in humans and/or animals. Although most apicomplexans parasitize within the host cell cytosols, Cryptosporidium resides on top of host cells, but it is embraced by a double-layer parasitophorous vacuole membrane derived from host cell. There is an electron-dense band to separate the parasite from host cell cytoplasm, making it as an intracellular but extracytoplasmic parasite. However, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Host actin has shown to be essential for the invasion and replication of apicomplexan parasites such as Cryptosporidium [43]. Our results were in line with previous cell culture and microscopy studies showing that Cryptosporidium forces the host actins to assemble and polymerise into plaque structures in order to complete the invasion process by sporozoites [44,45].…”
Section: Cryptosporidiosis Dynamics In the Gutsupporting
confidence: 91%
“…Host actin has shown to be essential for the invasion and replication of apicomplexan parasites such as Cryptosporidium [43]. Our results were in line with previous cell culture and microscopy studies showing that Cryptosporidium forces the host actins to assemble and polymerise into plaque structures in order to complete the invasion process by sporozoites [44,45].…”
Section: Cryptosporidiosis Dynamics In the Gutsupporting
confidence: 91%
“…Transcript levels were substantially higher in oocysts and sporozoites than in the intracellular stages, for example, transcript levels were 24.3-fold higher in sporozoites than in intracellular parasites 6 h post-infection (hpi) and 4.8-to 7.5-fold higher than the levels at 3, 12, 24, 48, and 72 hpi. The qRT-PCR assay was reliable because the transcriptomic profiles detected in parallel for three reference genes (CpEF1α, CpLDH, and CpTIPH) followed the same patterns as those previously reported (29,38,39). The native protein in C. parvum oocysts was also detected using Western blot analysis (Figure 5B).…”
Section: Cryptosporidium Parvum Rhomboid Peptidase 1 and Its Counterparts Are One Of The Three S54 Rhomboid-type Membrane Peptidases Pressupporting
confidence: 76%
“…Host actin has been shown to be essential for the invasion and replication of apicomplexan parasites such as Cryptosporidium [44]. Previous cell culture and microscopy studies have showed that Cryptosporidium forces the host actins to assemble and polymerise into plaque structures in order to complete the invasion process by sporozoites [45,46]. However, upregulation of actin as a result of parasite infection has not been previously reported.…”
Section: Cryptosporidiosis Dynamics In the Gutmentioning
confidence: 99%